2005
DOI: 10.1103/physreve.72.037302
|View full text |Cite
|
Sign up to set email alerts
|

Bubble dispenser in microfluidic devices

Abstract: This Brief Report presents experimental and computational results on bubble formation in microfluidic devices. Bubbles are generated at the right-angle intersection of four identical square microchannels. When the pressure gradient generated by the liquid flow dominates the pressure gradient generated by gas flow, the length of the produced confined bubbles follows a law based on the channel size and fluid volume fraction. This bubble production technique was used to produce monodisperse aqueous foam in two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 24 publications
8
92
0
1
Order By: Relevance
“…This mechanism was first proposed by Garstecki et al (2006), where the functional form V (Q) was observed experimentally. Cubaud et al (2005) observed a similar behaviour for bubble formation in a symmetric cross-junction. We verified this result for the drop volume with our numerical simulations.…”
Section: Resultssupporting
confidence: 62%
“…This mechanism was first proposed by Garstecki et al (2006), where the functional form V (Q) was observed experimentally. Cubaud et al (2005) observed a similar behaviour for bubble formation in a symmetric cross-junction. We verified this result for the drop volume with our numerical simulations.…”
Section: Resultssupporting
confidence: 62%
“…[29][30][31][32][33][34] In this particular configuration, dimensional analysis and physical arguments have provided with closed expressions for the scaling of the bubble size based on the different control parameters. 29,[32][33][34][35][36] However, although the proposed scaling laws are valid for practical purposes because they predict the bubble volume relatively well, a more detailed theoretical and numerical approach would be desirable to fully comprehend the bubble formation mechanisms. Making use of numerical simulations in the zero Reynolds number limit ͑Stokes flow͒, Jensen et al 37 have recently derived scaling laws to predict the volume of bubbles formed using the flow-focusing geometry that agree with previous experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics appears to offer a promising new route to fabrication of these materials, enabling the production of highly uniform droplets, bubbles, and particles in the 10-100 micrometer size range. By flowing two or more immiscible liquids into a microfluidic device, numerous authors have demonstrated the ability to make emulsion droplets, 1-3 gas bubbles, 4,5 solid polymeric particles, [6][7][8] and even more novel particles including double emulsions, 9 polymeric particles with arbitrary nonspherical shapes, 10 spherical colloidal shells, 11 and Janus particles. 10 The highly ordered packing of the monodisperse droplets has also been used to template porous materials.…”
Section: Introduction and Background On Tipstreamingmentioning
confidence: 99%